The Relationship of Family Support and Anxiety Level in Covid-19 Quarantine Patients in an Isolation Room in Bangli District - Renayani Ni Kadek; Ira Oktavia Siagian (Jurnal Kesehatan, 2022)
The psychological impact caused by COVID-19 is very diverse; one of the psychological effects that often arise is anxiety. Anxiety arises because of the fear of COVID-19 which may cause many negative impacts, from illness to death. Patients who experience anxiety require mental support from the family in order to increase the patient’ enthusiasm for life. The purpose of this study was to determine the relationship between family support and anxiety levels in COVID-19 quarantine patients. This study used a quantitative method, using Cross Sectional research design, with an observational approach. The population of this study was 58 COVID-19 quarantine patients, and the sampling method was total sampling technique. The measuring instrument used is the HARS questionnaire, while the data analysis used is the Spearman's rank test. The results of the univariate analysis of the family support variable showed that the category of respondents who lacked of family support was 22 (37.9%) respondents, while for the anxiety variable there were 28 (48.3%) respondents who experienced moderate anxiety. The results of the bivariate analysis using the Spearman's rank test obtained a p-value of 0.000 < 0.05 (α). Therefore, it can be concluded that there is a relationship between the support provided by the family and the level of anxiety.